Toxicidade do inseticida flupiradifurona no cérebro e intestino de Scaptotrigona postica (Latreille, 1807) (Hymenoptera, Apidae, Meliponini) e seus efeitos comportamentais - Castor, Rebeca Emanuelle da Silva (2025)
Bees are important and efficient pollinators of wild and agricultural plant species, but the population of these pollinators has been declining around the world. Among the various stressors responsible for this decline is the indiscriminate use of pesticides. Flupyradifurone, a pesticide released a few years ago in Brazil, was developed as a safer and less toxic alternative to neonicotinoid insecticides for the environment and non-target organisms such as bees. However, it is still necessary to understand the physiological and behavioral effects of this substance on native bees, since most studies with this pesticide use the Apis mellifera bee. In order to understand the effects of flupyradifurone on native bees, this study aimed to evaluate the influence of chronic oral exposure to an environmentally relevant concentration of flupyradifurone on the survival and locomotion behavior of Scaptotrigona postica, as well as to understand the impacts of this insecticide on the bees' brains and intestines. To carry out the survival bioassay, the bees were fed 50% m/m sucrose syrup containing the insecticide (exposed group) and only the syrup without the insecticide (control group) until the last individual died. For histopathological and behavioral evaluation, S. postica forager bees were exposed to flupyradifurone for 7 days and, after this period, individuals from the exposed and control groups were dissected to obtain organs and the individuals were filmed in the arena. It was observed that the presence of flupyradifurone does not interfere with bee survival, so that individuals from the control and exposed groups survived for a similar length of time. However, the insecticide is responsible for reducing the bees' locomotion behavior, which can compromise the tasks performed by the foragers in the colony. This behavioral change can be explained by the impact of the insecticide on the arrangement of the Kenyon cells (compacted and internal) that make up the internal neuronal part of the calyx of the pedunculated bodies, which are responsible for cognitive functions such as behavioral plasticity and associative learning. Exposure to the pesticide increased the distance between the Kenyon cells by between 1.9 and 2 times. In contrast, flupyradifurone did not negatively affect the morphology of the bees' midgut. Therefore, under laboratory conditions, the insecticide flupyradifurone interferes with Kenyon cells, potentially resulting in behavioral changes. However, these adverse effects do not interfere with bee survival, but may indirectly affect the performance of foraging activities within the colony after collecting floral resources in the field.